Application of the Cooperative Learning Model Jigsaw Technique in Efforts to Improve Learning Outcomes History for Class X Students of SMA Negeri 2 Rembang Teachings 2012/2013 - Nugroho, Bayu Setyo (Universitas Negeri Semarang, 2017)
This study aims to improve student learning outcomes by using more Berfariasi learning models, one of which is a jigsaw cooperative learning technique. Based on known results, prusiks students achieved mastery learning reaches 54.3% or 19 students completed with an average value of 70.7 after using the learning model Jigsaw cooperative learning techniques in skills I mastery learning students achieved 68.6% or 24 students completed with an average of 72.7 average. It can be concluded that with a history of knowing the Bahawa learning model, Jigsaw cooperative learning techniques can improve student learning outcomes in the classroom XH 2 Apex Senior High School.